Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak PBB Dalam Membayar Pajak Di Kelurahan The Hok, Kota Jambi. - Yulia Wulandari; Haitamy, Ery Bestary Al; Adinda, Pramesti Nurul (LP2M Politeknik Jambi, 2025)
This study aims to determine the extent of the influence of taxpayer knowledge and tax sanctions on taxpayer compliance. The population of this study is PBB taxpayers in The Hok Village, Jambi City. This type of research is quantitative with a survey method. The technique used in the data collection of this study is Purposive Sampling, the number of samples used is 100 samples. Data collection is by sharing several questionnaire statements. The result of this analysis is that taxpayers' knowledge and partial tax sanctions on taxpayers' compliance in paying Land and Building Tax have a positive and significant effect. Meanwhile, taxpayer knowledge and tax sanctions simultaneously on taxpayers' compliance in paying Land and Building Tax have a positive and significant effect.